Global ecological regionalization of 15 Illicium species: nature sources of shikimic acid - Xiang Zhang; Xiangxiao Meng; Jie Wu; Linfang Huang; Shilin Chen (BMC, 2018)
Abstract Background Illicium plants are relevant officinal and ornamental species that are native in Eastern Asia, and they are the main sources of shikimic acid. Shikimic acid is an important component of Tamiflu, which is recognized for its ability to resist avian influenza by the World Health Organization. To determine areas where 15 Illicium species can be grown and to understand the importance of species diversity, we should enhance the prediction of suitable areas. Methods In this study, the global potential distribution of 15 Illicium species was predicted using a geographic information system for global medicinal plants. Results Results showed that the possible suitable areas for these plants in China covered 1357.68 × 104 km2 (56%), and the second-largest area spanning 527.42 × 104 km2 was found in the United States. Illicium verum Hook, an edible species with the highest shikimic acid content among them, grew in areas of 59.92 × 104 (48%), 64.04 × 104 (19%), and 60.53 × 104 km2(18%) in China, the United States, and Brazil, respectively. Illicium.difengpi B. N. Chamg, an endangered species, was distributed in an area of 19.03 × 104 km2 or 95% of the total area in China. Conclusions This research provided a guarantee for the demand of Tamiflu, presented strategies that helped protect endangered species, and provided a reference for species cultivation and introduction.